Topological Properties of Solution Sets for Hilfer Fractional Nonlocal Delay Control Systems and Applications. (17th February 2022) - Jiang, Yirong; Chen, An; Li, Tingting
Abstract: The aim of this paper is to investigate the topological properties of mild solution sets for a control system described by Hilfer fractional delay evolution equations with nonlocal initial conditions. We firstly obtain the nonemptiness, the compactness and R δ -property of the mild solution set by applying Schauder's fixed point theorem, a fixed point theorem of nonconvex valued maps and the fractional calculus. Then we apply this obtained result to show that the presented control problem has a reachable invariant set under nonlinear perturbations. Furthermore, we also apply the obtained results to characterize the approximate controllability of the presented control problem. Finally, we present an example to illustrate the application of abstract results.